Novel Mutations in the DYNC1H1 Tail Domain Refine the Genetic and Clinical Spectrum of Dyneinopathies. Issue 3 (13th March 2015) - Peeters, Kristien; Bervoets, Sven; Chamova, Teodora; Litvinenko, Ivan; De Vriendt, Els; Bichev, Stoyan; Kancheva, Dahlia; Mitev, Vanyo; Kennerson, Marina; Timmerman, Vincent; De Jonghe, Peter; Tournev, Ivailo; et al.
Abstract : In this report, we have enriched the spectrum of mutations in the DYNC1H1 gene and their clinical manifestation. We demonstrate that dyneinopathies can present as an axonal form of peripheral neuropathy or a severe motoneuron disorder characterized by multiple congenital contractures and delayed motor milestones, without brain malformations. We provide experimental evidences that molecular defects in DYNC1H1 increase the interaction with its adaptor BICD2. ABSTRACT: The heavy chain 1 of cytoplasmic dynein (DYNC1H1) is responsible for movement of the motor complex along microtubules and recruitment of dynein components. Mutations in DYNC1H1 are associated with spinal muscular atrophy (SMA), hereditary motor and sensory neuropathy (HMSN), cortical malformations, or a combination of these. Combining linkage analysis and whole‐exome sequencing, we identified a novel dominant defect in the DYNC1H1 tail domain (c.1792C>T, p.Arg598Cys) causing axonal HMSN. Mutation analysis of the tail region in 355 patients identified a de novo mutation (c.791G>T, p.Arg264Leu) in an isolated SMA patient. Her phenotype was more severe than previously described, characterized by multiple congenital contractures and delayed motor milestones, without brain malformations. The mutations in DYNC1H1 increase the interaction with its adaptor BICD2. This relates to previous studies on BICD2 mutations causing a highly similar phenotype. Our findings broaden the genetic heterogeneity and refine the clinical spectrum of DYNC1H1, and have implications for molecular diagnostics of motor neuron diseases.